Development of the stakeholder marketing at the enterprises in transportation and logistic system - N.V. Popova; V.G. Shynkarenko (Marketing i Menedžment Innovacij, 2016)
The aim of the article is to form conceptual model of the stakeholders marketing development and its implementation mechanism at the enterprises in transportation and logistic system in cluster network. The results of the analysis. The stakeholders marketing development problem at the enterprises of transportation and logistic system (TLS)in Ukraine is connected with necessity to satisfy consumers’ needs more widely, because the interested sides impact the efficiency to give service in transport and logistics sphere. It is especially seen in cluster organizations, where stakeholders’ networks cooperate with each other. In order to see relation to stakeholders marketing and stakeholders approach in management, one carried out research of enterprises, transport and logistic organizations in Kharkiv region, which showed that enterprises have no information about stakeholders marketing, but most of them wish to understand and use it. Development of the stakeholders marketing at the transport and logistic system enterprises, which cooperate in the cluster, has its peculiarities, based on the fact that enterprises, consumers, partners and other stakeholders are connected with continual network. Their interests are observed as those ones, interconnected by the common aim. Interests conflict, appearing in the process of functioning, is solved through the dialogue. Enterprises are work in complicated system, which includes interconnection between subjects in cluster and outside it, based on trusting relations. All sides of the process to give and get transportation and logistic service, take part in creation of valuable. TLS enterprises make democratic marketing decisions,which are controlled by all stakeholders. Taking into account stakeholders marketing peculiarities, one suggested conceptual model of its development at the transportation and logistic system enterprises in cluster network. It includes formation of relations with all stakeholders, based on common interests, general objective and general actions for their achievement defining. Result of the stakeholders marketing introduction is cooperative valuable creation by means of qualitative transportation and logistic service, achieving of general and individual interests and problematic situations effective solving, receiving of benefits by means of the financial incomes and trusting relations setting in the stakeholder network. These results will help to form positive image both for the TLS enterprises and cluster on a whole, and also its location region. Under conditions of changeability, uncertainty, complexity and multiplicity in the modern world stakeholders marketing development will provide increase of the competitiveness at the transportation and logistic enterprises system. One suggests to evaluate results of stakeholders marketing development at the transportation and logistic system enterprises by such factors as stakeholders’ satisfaction level, all subjects’ profitability level in the cluster network, level of cooperation subjects’ trust, based on applications agreement and real actions, level of the enterprise and stakeholders’ competitiveness. Introduction of the stakeholders marketing development conceptual model at the enterprises from transportation and logistic system requires its realization effective mechanism. To make the model working, one suggests three components of its realization mechanism – organizational mechanism, marketing actions planning and realization mechanism and economic mechanism. By means of structure, responsible for stakeholders’ marketing introduction, one proposes to create marketing-center in the cluster. Its personnel must study effective integrity, trusting relations forming, develop empathy. Marketing center activity directions are defined. Сonclusions and directions of further researches. Under conditions of changeability, uncertainty, complexity and multiplicity in the modern world, new paradigm of the marketing provides business with flexibility, helps to form trusting relations, generates financial growing of all stakeholders. Perspectives for future studies are: to formalize complex interconnection between TLS enterprises and stakeholders in the cluster network and to agree their interests,to develop practical tools to use stakeholders marketing and to evaluate its results, and to solve problems concerning structures creation, which give opportunity to take into account all stakeholders’ interests.